THE EFFECT OF PRODUCT QUALITY AND SERVICE ON CONSUMER SATISFACTION QOUKA COFEE SURABAYA - Eddhinda Leandro Virgin Karenina; Eko Priyanto; Sri Tjondro Winarno (STKIP Singkawang, 2022)
Customer satisfaction is an important thing that must be considered by the company. By maintaining the quality of products and services, customer satisfaction will be achieved, with the achievement of customer satisfaction, the company will experience positive development and progress. Measurement of satisfaction is needed to find out what attributes need to be maintained and improved, so a research method is needed, namely Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The research was conducted by taking a sample of 100 respondents. The results of the analysis show that in the IPA calculation there are attributes of speed and aroma located in quadrant I, attributes of cleanliness, politeness, friendliness, taste and neatness are located in quadrant II, texture and color attributes are located in quadrant III, and the price attribute is in quadrant IV. The CSI calculation shows the figure of 83.65% which at the level of the figure states that consumers are in the very satisfied category.